Mengungkap Tradisi: Sistem Peralihan Harta Warisan di Kecamatan Kampar Utara - Putra, Deri Eka (Syakhsiyah Jurnal Hukum Keluarga Islam, 2024)
This study looks on the North Kampar District's customary law pertaining to the system of property transfer based on maternal descent. This kind of qualitative study seeks to explain the occurrences that take place. There are several strategies available to accomplish this aim. This approach typically makes use of pre-existing records, interviews, and observation. As a result, this study is empirical. Because the transfer of inherited assets in North Kampar District follows customs that have been handed down from the female or maternal lineage from generation to generation, the research's findings demonstrate that women are better suited to safeguard and take care of inherited assets. The assets acquired in this instance are known as soko assets, which include land, traditional homes, or gadang, and other kinds of assets.